2008
DOI: 10.1094/fg-2008-1104-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Small-Grain Forages for the Southern High Plains

Abstract: Information is lacking on the relative performance of small‐grain forage types grown for hay or silage on the High Plains of New Mexico and West Texas. Tests were conducted from 2004 to 2008 at Clovis, NM, to determine long‐term potential of common varieties and blends of species [wheat (Triticum aestivum L.), triticale (xTriticosecale), and oats (Avena sativa L.)] in an irrigated production system. Eleven entries were tested in at least 3 years, including exceptionally wet (2005) and dry (2006) years. In any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
39
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(52 citation statements)
references
References 8 publications
10
39
3
Order By: Relevance
“…The crops had different ( P < 0.01) NO 3 –N concentrations; however, all observed levels (54–692 mg kg −1 ) in these samples were considered safe for livestock consumption (Table 3). These data are consistent with those of Marsalis et al (2008) in New Mexico, who reported that winter triticale had superior forage production than winter wheat, but wheat generally had better forage quality than triticale.…”
Section: Characteristicssupporting
confidence: 90%
“…The crops had different ( P < 0.01) NO 3 –N concentrations; however, all observed levels (54–692 mg kg −1 ) in these samples were considered safe for livestock consumption (Table 3). These data are consistent with those of Marsalis et al (2008) in New Mexico, who reported that winter triticale had superior forage production than winter wheat, but wheat generally had better forage quality than triticale.…”
Section: Characteristicssupporting
confidence: 90%
“…In general, the forage yields at McGregor in 2005–2006 were lower than in the Thrall location in 2004–2005 due to persistent drought conditions. The amount of precipitation received at McGregor during the 2005–2006 season was ∼13.4 inches lower than Thrall during 2004–2005 and 8.2 inches lower than the long‐term average (Table 3), which resulted in a reduction in the respective dry matter yield for each crop species compared with the previous crop year, which is in agreement with Marsalis et al (2008). Dry matter yields for the small grain crop species ranged from 5925 to 4318 lb/acre (Fig.…”
Section: Forage Yieldsupporting
confidence: 82%
“…Croy (1983) also reported that ryegrass growth continued later in the spring beyond wheat and rye production, but adequate soil moisture and mild temperatures were necessary for dependable production. In general, wheat has earlier maturity than triticale under irrigated conditions of the Southern High Plains (Marsalis et al, 2008).…”
Section: Useful Conversionsmentioning
confidence: 99%
“…Sanderson et al (15) reported that differences among years in response to irrigation were likely due to precipitation amount, frequency, and distribution. Marsalis et al (9) concluded that variation in precipitation also affects dry matter yields of small grain forages. Saeed and El‐Nadi (14) found that frequent, light irrigations, such as those applied through a sprinkler, led to greater sorghum forage yield than heavier, infrequent irrigations, such as those applied with furrow irrigation, and that irrigation technique efficiency must be assessed as water for irrigation becomes more scarce.…”
Section: Evaluating Forage Yields Of Furrow‐irrigated Sorghum Cultivarsmentioning
confidence: 99%